Assessing Employee Work Behavior: The Influence of Leadership Style and Commitment - Marsuhin Marsuhin (Trescode Green Organization, 2024)
This study aims to understand the extent to which leadership style and employee commitment influence their work behavior at Koperasi Sentral Asia, Lumajang. In this study, data was collected through questionnaires filled out by the cooperative's employees. The analysis was conducted using multiple linear regression to determine the relationship between the variables under study. The results show that employee commitment has a significant positive impact on their work behavior. This means that the higher the employees' commitment to the organization, the better their work behavior. On the other hand, leadership style, although tested, did not have a significant effect on work behavior. However, when both leadership style and commitment were tested simultaneously, they showed a significant impact on employees' work behavior. This indicates that although leadership style individually does not have an impact, in combination with commitment, it contributes to improving work behavior. These findings provide insights for the management of Koperasi Sentral Asia to focus more on strengthening employee commitment as a primary strategy for enhancing productivity and work behavior quality. Additionally, an approach to leadership that aligns with employees' needs should also be considered to support synergy between the two aspects.